Photography, Music and Memory - Pickering, Michael. author. aut Link
X, 211 p.
Keywords: This book explores how photography and recorded music act as vehicles or catalysts in processes of remembering, and how they are regarded, treated, valued and drawn upon as resources connecting past and present in everyday life. It does so via two key concepts: vernacular memory and the mnemonic imagination.